Identification of the Ω4499 Regulatory Region Controlling Developmental Expression of a Myxococcus xanthus Cytochrome P-450 System - Fisseha, Makda (American Society for Microbiology, 1999)
Ω4499 is the site of a Tn5 lac insertion in the Myxococcus xanthus chromosome that fuses lacZ expression to a developmentally regulated promoter. Cell-cell interactions that occur during development, including C signaling, are required for normal expression of Tn5 lac Ω4499. The DNA upstream of the Ω4499 insertion has been cloned, and the promoter has been localized. Analysis of the DNA sequence downstream of the promoter revealed one complete open reading frame and a second partial open reading frame that is interrupted by Tn5 lac Ω4499. The predicted products of these open reading frames are highly similar to reductase and oxidase components of bacterial cytochrome P-450 systems, which allow catabolism or anabolism of unusual compounds. However, the function of the gene products of the Ω4499 locus remains unclear because M. xanthus containing Tn5 lac Ω4499 exhibits no apparent defect in growth, developmental aggregation, fruiting body formation, or sporulation. Deletion analysis of the Ω4499 regulatory region showed that multiple DNA elements spanning more than 500 bp upstream of the transcriptional start site contribute to developmental promoter activity. At least two DNA elements, one downstream of −49 bp and one between −49 and −218 bp, boosted activity of the promoter in response to intercellular C signaling. Three sequences in the Ω4499 promoter region, centered at −55, −33, and −1 bp, nearly match a 7-bp sequence found in other C signal-dependent promoters. We propose that these sequences, matching the consensus sequence 5′-CAYYCCY-3′, be called C box sequences, and we speculate that these sequences are cis-acting regulatory elements important for the expression of M. xanthus genes that depend upon intercellular C signaling during development.